Thickness Effect of CuAlTe2 Thin Films on Morphological, Structural and Visual Properties - Hassan, Noor A.; Khudayer, Iman Hameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
CuAlTe2 thin films were evaporation on glass substrates using the technique of thermal evaporation at different range of thickness (200,300,400and500) Â±2nm. The structures of these films were investigated by X-ray diffraction method; showing that films possess a good crystalline in tetragonal structure. AFM showed that the grain size increased from (70.55-99.40) nm and the roughness increased from (2.08-3.65) nm by increasing the thickness from (200-500) nm. The optical properties measurements, such as absorbance, transmtance, reflectance, and optical constant as a function of wavelength showed that the direct energy gap decreased from (2.4-2.34) eV by the gain of the thickness.